Anxiety and Depressive Symptoms in the New Life With COVID-19: A Comparative Cross-Sectional Study in Japan Rugby Top League Players - Yasutaka Ojio; Asami Matsunaga; Shin Kawamura; Masanori Horiguchi; Goro Yoshitani; Kensuke Hatakeyama; Rei Amemiya; Ayako Kanie; Chiyo Fujii (Frontiers Media S.A., 2022)
Objectives: The primary objective is to compare the prevalence of mental health problems, including psychological distress, anxiety and depressive symptoms in Japan Rugby Top League players in the new life with COVID-19 with those evaluated before COVID-19.Methods: An observational comparative web-based cross-sectional study was employed for Japan Rugby Top League players. We compared the data from 220 Japanese and 7 foreign players during the new life with COVID-19 with the data from before COVID-19, which was obtained from 233 Japanese and 18 foreign players. We measured anxiety and depression symptoms with the validated Kessler-6, which has been widely used in clinical and research settings among different populations. To investigate the distribution of K6 score and whether there are discrete clusters or not, we conducted the two-step cluster analysis.Results: In the new life with COVID-19, 15.0% of players reported mild symptoms, which was significantly lower than the 32.3% of players before COVID-19. The prevalence of moderate and severe symptoms was 6.7 and 3.5%, respectively, in the group during the new life with the COVID-19, and 4.8 and 5.2% in the pre-COVID-19 group, with no significant difference. A two-step cluster analysis supported the existence of these two qualitatively different clusters in both groups.Conclusions: With the spread of new lifestyles related to COVID-19, some rugby players may have improved mental health status due to changes in their daily living environment. Such environmental adjustments alone may not have been sufficient to change the mental health status of others. Rugby players or their teams may require mental health professionals and systems that ensure rest, adjust the environment, and sustainably provide more professional care.